Effects of Pregnancy Anesthesia on Fetal Nervous System - Li, Xingyue; Jiang, Xi; Zhao, Ping (Frontiers in Pharmacology, 2021)
The effects of general anesthetics on the developing brain have been concerned in the medical field and even in the public, and most researches focus on infancy and childhood. In recent years, with the continuous development of medical technology, the number of operations in pregnancy is increasing, however, the studies on general anesthesia during pregnancy are relatively lacking. The mid-trimester of pregnancy is a critical period, which is regarded as a safety period for surgery, but it is a fragile period for the development of central nervous system and particularly sensitive to the impact of the environment. Our research group found that general anesthesia may have adverse effects on fetal neurodevelopment during the mid-trimester. Therefore, in this review, we summarized the characteristics of anesthesia during pregnancy, and the related researches on the anesthesia’s impacts on the development of central nervous system were introduced.